Mediation: court annexed - Ali Mohamed, Ashgar Ali; Rosli, Muhammad Noor Firdaus (The Malaysian Current Law Journal Sdn Bhd, 2020)
This chapter discusses on the application of mediation in the ordinary courts of law in Malaysia with reference to civil matters.